2016
DOI: 10.1007/s00784-016-1769-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alendronate on the progression of periodontitis induced by Porphyromonas gingivalis and Fusobacterium nucleatum: a study in rats

Abstract: ALN could be a potential therapeutic approach when associated with periodontal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
1
5
0
1
Order By: Relevance
“…These results agree with previous studies in which treatment with zoledronate attenuated alveolar bone loss, increased total bone volume and density 16,18 . Additionally, other authors have shown lower alveolar bone loss with other types of bisphosphonates, both locally and systemically applied, in animals 8,39,40 …”
Section: Discussionsupporting
confidence: 92%
“…These results agree with previous studies in which treatment with zoledronate attenuated alveolar bone loss, increased total bone volume and density 16,18 . Additionally, other authors have shown lower alveolar bone loss with other types of bisphosphonates, both locally and systemically applied, in animals 8,39,40 …”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the oral administration of alendronate to treat osteoporosis has shown to have a 0% to 0.4% chance of inducing ONJ [ 88 ]. Consequently, several studies have investigated the beneficial effects of alendronate administration to manage experimental periodontitis in rats [ 35 , 37 , 89 , 90 ] and PD in clinical trials [ 91 93 ]. Some of the described studies are described in table 2 .…”
Section: Bisphosphonatesmentioning
confidence: 99%
“…However, to induce the same lesion, this method may need a longer time (8,9). A combination of ligature and inoculation of P. gingivalis has been reported to induce alveolar bone loss in the rat model (10). The combination of ligature with a pathogenic product, such as lipopolysaccharide from P. gingivalis, which would accelerate the process, is not well described.…”
Section: Introductionmentioning
confidence: 99%